PENGETAHUAN, SIKAP DAN PERILAKU PADA KASUS DEMAM BERDARAH DENGUE DI KECAMATAN MANDIRAJA TAHUN 2022 - Bayu Suseno; Putri Harfianti (Jurnal Ilmiah Medsains, 2022)
Environmentally Based Diseases (PBL) is a health problem that is still common in the world, including in Indonesia, one of the PBLs that is still a problem is DHF. Based on data from the Banjarnegara Health Office, the highest dengue cases in 2020 were in Mandiraja District with 39 cases. Based on data from the Mandiraja 2 Public Health Center UPTD, the highest prevalence of DHF was  in  Purwasaba  Village.  The  purpose  of  this  study  was  to  determine  and describe the description of knowledge, attitudes, and behavior in cases of DHF in Purwasaba Village, Mandiraja District. This research is included in descriptive research with cross sectional approach. The population in this study was 63 houses with respondent criteria, namely dengue patients diagnosed in January-March 2022, and local residents with a radius of 200 m in RT 03 RW 03 Purwasaba Village, Mandiraja District, with purposive sampling using sampling. The data used in this study are primary data obtained from questionnaires and field observations as well as secondary data from previous studies. Based on the results of the study obtained data that respondents with an age range of 36-45 years 31.7%, female respondents 66.7%, most of the respondents' education levels in the study were 36.5% elementary school graduates,  most  of  the  respondents' occupations were  as follows: housewives 42.9%, the knowledge of most of the respondents is good 88.9%, the attitude of the respondents is classified as good 88.9% and the behavior of the respondents is classified as positive 55.6%. Based on the results of data processing, it is known that in the case of DHF in Purwasaba Village, Mandiraja District, they have  good knowledge, behave well, and behave positively. The community further improves behavior regarding PSN  DHF and  health  workers  further  improve  health  promotion,  namely  by providing counseling about DHF so that public knowledge about DHF increases and by holding activities to eradicate mosquito nests.